Kontroversi Pernikahan Beda Agama di Indonesia - Riu Zaldi Siregar; Uswatun Hasanah (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
This study examines the legal provisions regarding interfaith marriage in Indonesia from the perspective of Islamic law and national law. The focus lies on the differences and points of convergence between the two legal systems in assessing the validity of marriages conducted between couples of different religions. This research employs a library research method with a normative-comparative approach, analyzing primary sources such as the Qur’an, Hadith, the Compilation of Islamic Law (KHI), Law Number 1 of 1974 on Marriage, as well as relevant court decisions. The results show that Islamic law explicitly prohibits interfaith marriage, particularly between a Muslim woman and a non-Muslim man, as it contradicts the principles of faith and the objectives of marriage in Islam. Meanwhile, national law through Law Number 1 of 1974 stipulates that a marriage is valid only if conducted according to the laws of each religion and belief, which implicitly rejects the legality of interfaith marriage. In practice, however, some individuals seek legal loopholes through human rights interpretations or by registering their marriages abroad. Therefore, both Islamic and national law share the same goal: to preserve the sanctity of marriage and maintain social harmony based on the divine values upheld by the Indonesian nation.